Avaliação de um procedimento para ensino da implementação de tentativas discretas a aplicadores ABA - Borges, Mariana (2023)
The Behavioral Skills Training (BST) is a widely used procedure in staff training in the field of Applied Behavior Analysis (ABA). BST has been established as a best practice strategy for training ABA therapy implementers and is effective in the training and supervision of therapists using Discrete Trial Training (DTT) to teach skills to individuals with autism. This study aimed to evaluate a modality of BST that was used to train implementers in the execution of a DTT teaching procedure specifically designed for training auditory-visual conditional discriminations in children with autism. Using a single-subject, design three undergraduate Psychology students participated in a six-phase training procedure: 1) baseline, which consisted in the reading of the procedure followed by an evaluation of the student's application with a confederate; 2) instruction, which participants watched video lectures and answered related quizzes; 3) video modeling, which students watched videos of the researcher applying trials to a confederate and directly with a child; 4) role-play, which consisted of a new evaluation of DTT application performance with the confederate; 5) feedback, which consisted in informing the participant of their performance in the application with the confederate; and 6) generalization, which consisted in the direct application with a child to evaluate the participants' performance in a real interaction situation. All study sessions were recorded to collect, analyse data and evaluate interobserver agreement. The results indicated that two participants required exposure to two role-play sessions and one feedback session to achieve an 80% mastery criterion. None of the participants achieved the learning criterion after the instruction and video modeling phases. One participant did not achieve the learning criterion. The results are consistent with the literature regarding the effectiveness of the feedback component in BST. Ultimately, the usefulness of training protocols for clinical staff in terms of effectiveness and resource efficiency is discussed.